A laser processed ice-repellent wear-resistant micro-nano layered structure and preparation method thereof

The layer of concave pit structure is made on the aluminum alloy tablet through femtosecond laser processing and boiling water treatment, and fluorosis is performed, which solves the problem of poor ice sticking strength and abrasion resistance at low temperature at low temperature. Ice and mechanical wear resistance.

CN118682291BActive Publication Date: 2025-01-21SOUTHWEST UNIV OF SCI & TECH SICHUAN TIANFU NEW AREA INNOVATION RES INST +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410746927.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-11
Publication Date
2025-01-21
Estimated Expiration
2044-06-11

AI Technical Summary

Technical Problem

The existing superhydrophobic surfaces are easily transformed from the Cassie-Baxter state to the Wenzel state at low temperatures, increasing the adhesion strength of ice, and poor wear resistance, making it difficult to maintain anti-icing performance in complex environments.

Method used

The periodic layered concave pits structure is prepared on the aluminum alloy tablets through femtosecond laser processing, and a densely distributed sub -micron -shaped structure is formed through boiling water treatment. The fluoride is finally carried out to obtain ultra -hydrophobicity and mechanical wear resistance.

Benefits of technology

The Cassie-BAXTER state that maintains stable at low temperatures, reduce ice adhesion strength, extend the freezing time, and maintain good wear resistance after multiple wear, suitable for aircraft to prevent ice and ice.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118682291B_ABST
    Figure CN118682291B_ABST
Patent Text Reader

Abstract

The present invention discloses a laser-processed ice-phobic wear-resistant micro-nano layered structure and a preparation method thereof, comprising: a substrate, the surface of which is processed with layered pits arranged in a periodic array, the surface and interior of the layered pits are randomly distributed with micron-sized agglomerated particle structures, and the surfaces of the layered pits and the micron-sized agglomerated particles are closely arranged with submicron-sized flaky structures; the surface of the substrate is fluorinated and modified. The ice-phobic wear-resistant micro-nano layered structure of the present invention is a micro-nano multi-level composite structure, and the surface of the substrate has good mechanical durability. After multiple wear, its layered structure remains basically unchanged. At the same time, the surface of the substrate also has excellent ice-phobic performance, and its ice adhesion strength can be as low as 1.4kPa. Even after multiple sandpaper wear, its ice adhesion strength can still be maintained below 10kPa, and it has good reusability and self-cleaning properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of metal surface laser processing and ice prevention and deicing. More specifically, the present invention relates to a laser processed ice-repellent and wear-resistant micro-nano layered structure and a preparation method thereof. Background Art

[0002] In the cold winter, ice formation is common and has many negative effects on people's lives. How to remove the accumulated ice efficiently and quickly has become an important issue of general concern. Traditional deicing technologies such as chemical deicing or vibration deicing have the disadvantages of high energy consumption and low efficiency. Therefore, it is necessary to design new anti-icing / deicing strategies to prevent the adverse effects of ice formation.

[0003] Inspired by natural elements such as rose petals and lotus leaves, superhydrophobic surfaces have attracted great attention due to their excellent water-repellent properties. In recent years, biomimetic superhydrophobic surfaces have been widely used in the field of anti-icing and de-icing because they do not require external energy consumption. However, at low temperatures, superhydrophobic surfaces easily transform from the Cassie-Baxter state to the Wenzel state, which inevitably increases the adhesion strength of ice and hinders anti-icing / de-icing applications. In addition, the wear resistance of superhydrophobic surfaces is generally poor, and they are easily damaged by wear in actual complex environments, which in turn causes the failure of the surface's anti-icing and de-icing properties. Therefore, designing a superhydrophobic surface that maintains a stable Cassie-Baxter state, has ultra-low ice adhesion strength, and exhibits excellent mechanical durability remains a huge challenge. Summary of the invention

[0004] An object of the present invention is to solve at least the above problems and / or disadvantages and to provide at least the advantages which will be described hereinafter.

[0005] In order to achieve these purposes and other advantages according to the present invention, a method for preparing a laser-processed ice-phobic wear-resistant micro-nano hierarchical structure is provided, and the steps are as follows:

[0006] S1. Using a femtosecond laser to process a micro-cone array of the same size and spacing on the surface of a substrate, a surface with distributed micro-cones and smaller cluster structures is obtained; the laser beam of the femtosecond laser is perpendicular to the surface of the substrate, and the laser beam scans the surface line by line in a scanning path of perpendicular cross lines;

[0007] S2. Using a femtosecond laser to process a micro-pit structure of uniform size on the top of the micro-cone to obtain a layered pit structure and a smaller cluster structure, wherein the laser beam of the femtosecond laser is perpendicular to the substrate surface, and the laser beam is scanned point by point on the surface in a parallel manner;

[0008] S3, using a boiling water treatment method, immersing the substrate treated by S2 in boiling water for a certain period of time to obtain a densely distributed submicron-level flaky structure on the surface of the substrate;

[0009] S4. Performing fluorination treatment on the substrate treated in S3.

[0010] Preferably, in said S1, the spot diameter of the femtosecond laser is 10-20 μm, the pulse energy is 150-250 mW, the scanning speed is 0.001-0.004 m / s, and the scanning interval is 40-80 μm.

[0011] Preferably, in S2, the spot diameter of the femtosecond laser is 10-20 μm, the pulse energy is 90-130 mW, the scanning time is 18000-32000 μs, and the scanning interval is 40-80 μm.

[0012] Preferably, in S3, the boiling water treatment time is 60 to 180 minutes, and the boiling water temperature is 100 to 130°C.

[0013] Preferably, in S4, the substrate surface is fluorinated by using low surface energy 1H,1H,2H,2H-perfluorodecyltriethoxysilane for modification.

[0014] Preferably, the specific method for fluorination treatment of the substrate surface comprises: immersing the substrate in a mixture of 1H,1H,2H,2H-perfluorodecyltriethoxysilane and anhydrous ethanol, the volume ratio of 1H,1H,2H,2H-perfluorodecyltriethoxysilane and anhydrous ethanol being 1:50, and the immersion time being 2 to 4 hours.

[0015] An ice-phobic and wear-resistant micro-nano layered structure, comprising:

[0016] A substrate, the surface of which is processed with layered pits arranged in a periodic array, the surface and interior of the layered pits are randomly distributed with micron-scale clustered particle structures, and the surfaces of the layered pits and the micron-scale clustered particles are closely arranged with submicron-scale flaky structures;

[0017] The surface of the substrate is modified by fluorination.

[0018] Preferably, the substrate is an aluminum sheet or an aluminum alloy sheet with a thickness greater than 120 μm.

[0019] Preferably, the stratification pits are of the same size, with a stratification pit height of 20 to 90 μm, a stratification pit bottom diameter of 20 to 60 μm, a center distance between adjacent stratification pits of 20 to 120 μm, a central pit depth at the top of the stratification pit of 10 to 60 μm, and a central pit diameter of 10 to 40 μm.

[0020] An application of an ice-phobic and wear-resistant micro-nano layered structure, wherein the ice-phobic and wear-resistant micro-nano layered structure is applied to an aircraft aluminum skin or an aluminum alloy skin to achieve ice protection and deicing on the aircraft surface.

[0021] The present invention has at least the following beneficial effects:

[0022] The laser-processed ice-repellent and wear-resistant micro-nano layered structure and its preparation method provided by the present invention imitate the super-hydrophobicity of lotus leaves and the wear resistance of rose petals, and adopt a combination of femtosecond laser processing and boiling water treatment to prepare a micro-nano layered pit structure with precise and controllable morphology on an aluminum alloy sheet, and finally fluorination modification makes the surface super-hydrophobic. The presence of the multi-level structure in the micro-nano layered pit structure ensures the stability of the Cassie-Baxter state of the surface at low temperatures, reduces the ice adhesion strength, and thus achieves a good ice-repellent effect. In addition, the micro-nano layered pit structure provides mechanical support for the surface, avoids damage to the micro-nano structure inside the micro-pit, and improves the mechanical wear resistance of the surface.

[0023] The present invention utilizes the cutting-edge bionics principle, has a simple preparation process, low cost, and can precisely control the structure, so that it can achieve efficient and large-area preparation, and can simultaneously achieve good anti-icing, ice-repelling and mechanical wear resistance. In terms of anti-icing, the surface of the micro-nano layered pit structure has a smaller solid-liquid contact area, which can effectively reduce the heat transfer efficiency and delay the freezing of water droplets on its surface, with the freezing time up to 2 hours; in terms of ice repelling, the ice adhesion strength on the surface can be as low as 1.4kPa. The low ice adhesion strength can quickly remove the accumulated ice on the surface under the action of external forces such as tilt, breeze, and vibration, thereby maintaining a good ice repelling effect; in terms of mechanical wear resistance, after multiple wear and tear, the micro-nano layered structure of the surface remains basically unchanged, and even after multiple sandpaper wear, its ice adhesion strength can still be maintained below 10kPa, and it can be reused many times, which has important application potential in the field of aircraft anti-icing and deicing.

[0024] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 Electron microscope images of the hierarchical pit structure, micro-cluster structure and submicron-level sheet structure of the ice-phobic wear-resistant micro-nano hierarchical structure of the present invention;

[0026] Figure 2 This is a delayed icing function diagram of the ice-phobic and wear-resistant micro-nano hierarchical structure of the present invention, A is the surface of the present invention, and B is the untreated unstructured aluminum alloy surface;

[0027] Figure 3This is an electron microscope image of the ice-phobic wear-resistant micro-nano hierarchical structure after wear;

[0028] Figure 4 A comparison diagram of the cross-sectional profiles of the ice-phobic wear-resistant micro-nano hierarchical structure before and after wear of the present invention;

[0029] Figure 5 This is a schematic diagram of the pit structure processed on the aluminum alloy substrate in Comparative Example 1 of the present invention;

[0030] Figure 6 This is a schematic diagram of a micro-cone structure processed on an aluminum alloy substrate in Comparative Example 2 of the present invention;

[0031] Figure 7 It is a bar graph of low ice adhesion strength of comparative examples 1-2 and embodiment 3;

[0032] Figure 8 This is the wear resistance diagram of Comparative Examples 1-2 and Example 3. DETAILED DESCRIPTION

[0033] The present invention is further described in detail below in conjunction with the accompanying drawings so that those skilled in the art can implement the invention with reference to the description.

[0034] It should be understood that the terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.

[0035] The micropapillary structure on the surface of lotus leaves plays a crucial role in its superhydrophobicity. However, this surface structure is easily damaged by wear and tear and loses its superhydrophobicity. The groove structure on the surface of rose petals can protect the micro-nanostructure inside the groove from damage and has good mechanical durability.

[0036] The present invention imitates the surface structure of lotus leaves and rose petals, and uses femtosecond laser processing combined with boiling water treatment to process a micro-nano layered structure on the surface of an aluminum sheet or an aluminum alloy sheet, including using femtosecond laser processing to form a periodically distributed layered pit structure, and micron-sized agglomerates of particles of different sizes are randomly distributed on the surface of the layered pits, and a densely arranged submicron-level sheet structure is grown on the surface of the layered pits and micro-agglomerates by boiling water treatment (see Figure 1 ), and then fluorinating the surface of the aluminum sheet or aluminum alloy sheet to make the surface super hydrophobic and ice-phobic, thereby obtaining an ice-phobic and wear-resistant micro-nano hierarchical structure;

[0037] Among them, the thickness of the aluminum sheet or aluminum alloy sheet is greater than 120μm; the size of the stratified pits is the same, the height of the stratified pits is 20-90μm, the diameter of the bottom of the stratified pits is 20-60μm, and the center distance between the stratified pits is 20-120μm; the central pits at the top of the stratified pits are the same size, the height of the central pits is 10-60μm, the diameter of the central pits is 10-40μm, and the center distance between two adjacent central pits is 20-120μm; the diameter of the micron-sized agglomerated particles is 1-6μm; the surface fluorination modification adopts low surface energy 1H,1H,2H,2H-perfluorodecyltriethoxysilane for modification.

[0038] The specific scheme proposed by the present invention is described in more detail with reference to several specific embodiments below.

[0039] Embodiment 1:

[0040] The present embodiment provides an ice-phobic and wear-resistant micro-nano layered structure, which is arranged on an aluminum alloy substrate with a thickness of 150μm. There is a periodic layered pit structure of the same size on the surface of the aluminum alloy, the height of the layered pit is 25μm, the bottom diameter of the layered pit is 50μm, and the center spacing of the layered pit is 60μm; the center pit diameter of the top of the layered pit is 25μm, the center pit depth of the top of the layered pit is 15μm, and the center spacing of the center pits of the tops of two adjacent layered pits is 60μm. Smaller micron-sized agglomerated particles are randomly distributed on the surface of the layered pits, and the diameter of the micron-sized agglomerated particles ranges from 1 to 6μm; submicron-sized flaky structures are closely arranged on the surfaces of the layered pits and the micron-sized agglomerated particles, and the width of the submicron-sized flaky structures is 100 to 400nm.

[0041] The preparation method of the above-mentioned ice-phobic wear-resistant micro-nano hierarchical structure comprises the following steps:

[0042] 1) A femtosecond laser was used to process a periodic micro-cone structure of the same size and spacing on the surface of an aluminum alloy substrate to obtain a surface with distributed micro-cones and micro-cluster structures. The laser beam was perpendicular to the surface of the aluminum alloy substrate, and the laser beam was scanned line by line on the surface of the aluminum alloy substrate in a vertical cross line manner; the laser spot diameter was 15 μm, the pulse energy was 200 mW, the scanning spacing was 60 μm, and the scanning speed was 0.002 m / s.

[0043] 2) A micro-pit structure of uniform size is processed on the top of the micro-cone by using a femtosecond laser to obtain a layered pit structure and a smaller micro-cluster structure. The laser beam of the femtosecond laser is perpendicular to the surface of the aluminum alloy substrate, and the laser beam scans the surface point by point in a parallel manner; the laser spot diameter is 15 μm, the pulse energy is 100 mW, the scanning time is 26000 μs, and the scanning interval is 60 μm.

[0044] 3) The aluminum alloy substrate treated in step 2) is immersed in boiling water at 120° C. for 60 minutes by boiling water treatment, and densely distributed submicron-scale flaky structures are obtained on the surface of the aluminum alloy substrate.

[0045] 4) The surface of the aluminum alloy substrate treated with boiling water is fluorinated using low surface energy 1H,1H,2H,2H-perfluorodecyltriethoxysilane to modify it into a superhydrophobic surface. The specific method of the surface fluorination treatment of the aluminum alloy substrate includes: immersing the aluminum alloy substrate in a mixed solution of 1H,1H,2H,2H-perfluorodecyltriethoxysilane and anhydrous ethanol, the volume ratio of 1H,1H,2H,2H-perfluorodecyltriethoxysilane to anhydrous ethanol is 1:50, and the immersion time is 2 hours.

[0046] See also Figure 2 In order to verify the anti-icing ability of the ice-phobic and wear-resistant micro-nano layered structure, the sample was horizontally pasted on a cooling table, a 10μL drop of ultrapure water was dropped on the surface of the layered structure aluminum alloy substrate, and the power of the cooling table was turned on. The time for the droplet to completely freeze was 124 minutes, while the freezing time of the droplet on the surface of the unstructured aluminum alloy sheet was 6 minutes, and the freezing time of the droplet was extended by nearly 2 hours.

[0047] Embodiment 2:

[0048] The present embodiment provides an ice-phobic and wear-resistant micro-nano layered structure, which is arranged on an aluminum alloy substrate with a thickness of 150μm, and has a periodic layered pit structure of the same size on the surface of the aluminum alloy, the height of the layered pits is 25μm, the bottom diameter of the layered pits is 50μm, and the center spacing of the layered pits is 60μm; the pit diameter at the top of the layered pits is 25μm, the pit depth at the top of the layered pits is 15μm, and the center spacing of the pits at the top of the layered pits is 60μm, and smaller micron-sized agglomerated particles are randomly distributed on the surface of the layered pits, and the diameter of the micron-sized agglomerated particles ranges from 1 to 6μm; submicron-sized flaky structures are closely arranged on the surface of the layered pits and the micron-sized agglomerated particles, and the width of the submicron-sized flaky structures is 100 to 400nm.

[0049] The preparation method of the above-mentioned ice-phobic wear-resistant micro-nano hierarchical structure comprises the following steps:

[0050] 1) A femtosecond laser was used to process a periodic micro-cone structure of the same size and spacing on the surface of the aluminum alloy to obtain a surface with distributed micro-cones and micro-cluster structures. The laser beam was perpendicular to the surface of the aluminum alloy substrate, and the laser beam was scanned line by line on the surface of the aluminum alloy substrate in a vertical cross line manner; the laser spot diameter was 15 μm, the pulse energy was 200 mW, the scanning spacing was 60 μm, and the scanning speed was 0.002 m / s.

[0051] 2) A micro-pit structure of uniform size is processed on the top of the micro-cone by using a femtosecond laser to obtain a layered pit structure and a smaller micro-cluster structure. The laser beam of the femtosecond laser is perpendicular to the surface of the aluminum alloy substrate, and the laser beam is scanned point by point on the surface of the aluminum alloy substrate in a parallel manner; the laser spot diameter is 15 μm, the pulse energy is 100 mW, the scanning time is 26000 μs, and the scanning interval is 60 μm.

[0052] 3) The aluminum alloy treated in step 2) is immersed in boiling water at 120° C. for 60 minutes to obtain a densely distributed submicron-scale lamellar structure on the surface of the aluminum alloy substrate.

[0053] 4) The surface of the aluminum alloy substrate treated with boiling water is fluorinated using low surface energy 1H,1H,2H,2H-perfluorodecyltriethoxysilane to modify it into a superhydrophobic surface. The specific method of the surface fluorination treatment of the aluminum alloy substrate includes: immersing the aluminum alloy substrate in a mixed solution of 1H,1H,2H,2H-perfluorodecyltriethoxysilane and anhydrous ethanol, the volume ratio of 1H,1H,2H,2H-perfluorodecyltriethoxysilane to anhydrous ethanol is 1:50, and the immersion time is 2 hours.

[0054] In order to verify the ice-phobic performance of the ice-phobic wear-resistant micro-nano hierarchical structure, the sample was placed horizontally in a refrigerator at a temperature of -18°C and a relative humidity of 80%. A 6mm×6mm×30mm transparent uncovered square tube was used as a mold and placed on the sample. Ultrapure water was added to the mold and frozen for 4 hours until it was completely frozen, and then the icicle was pushed at a constant speed with a thrust gauge. The peak force required to push down the icicle was recorded, and its ice adhesion strength was calculated to be 1.4kPa.

[0055] Embodiment 3:

[0056] The present embodiment provides an ice-phobic and wear-resistant micro-nano layered structure, which is arranged on an aluminum alloy substrate with a thickness of 150μm, and has a periodic layered pit structure of the same size on the surface of the aluminum alloy, the height of the layered pits is 25μm, the bottom diameter of the layered pits is 50μm, and the center spacing of the layered pits is 60μm; the pit diameter at the top of the layered pits is 25μm, the pit depth at the top of the layered pits is 15μm, and the center spacing of the pits at the top of the layered pits is 60μm, and smaller micron-sized agglomerated particles are randomly distributed on the surface of the layered pits, and the diameter of the micron-sized agglomerated particles ranges from 1 to 6μm; submicron-sized flaky structures are closely arranged on the surface of the layered pits and the micron-sized agglomerated particles, and the width of the submicron-sized flaky structures is 100 to 400nm.

[0057] The preparation method of the above-mentioned ice-phobic wear-resistant micro-nano hierarchical structure comprises the following steps:

[0058] 1) A femtosecond laser was used to process a periodic micro-cone structure of the same size and spacing on the surface of an aluminum alloy to obtain a surface with distributed micro-cones and micro-cluster structures. The laser beam was perpendicular to the surface, and the laser beam was scanned line by line on the surface in a vertical cross line manner; the laser spot diameter was 15 μm, the pulse energy was 200 mW, the scanning spacing was 60 μm, and the scanning speed was 0.002 m / s.

[0059] 2) A micro-pit structure of uniform size is processed on the top of the micro-cone by using a femtosecond laser to obtain a layered pit structure and a smaller micro-cluster structure. The laser beam of the femtosecond laser is perpendicular to the surface, and the laser beam scans the surface point by point in a parallel manner; the laser spot diameter is 15 μm, the pulse energy is 100 mW, the scanning time is 26000 μs, and the scanning interval is 60 μm.

[0060] 3) The surface treated in step 2) is immersed in boiling water at 120° C. for 60 minutes by boiling water treatment to obtain densely distributed submicron-scale lamellar structures on the surface of the aluminum alloy.

[0061] 4) The aluminum alloy surface treated with boiling water is fluorinated with low surface energy 1H,1H,2H,2H-perfluorodecyltriethoxysilane to modify it into a superhydrophobic surface. The specific method of the aluminum alloy substrate surface fluorination treatment includes: immersing the aluminum alloy substrate in a mixture of 1H,1H,2H,2H-perfluorodecyltriethoxysilane and anhydrous ethanol, the volume ratio of 1H,1H,2H,2H-perfluorodecyltriethoxysilane to anhydrous ethanol is 1:50, and the immersion time is 2 hours.

[0062] In order to verify the mechanical wear resistance of the ice-phobic wear-resistant micro-nano hierarchical structure, 1000-grit sandpaper was placed under the sample, and the sample was pasted on the bottom of a 100g weight to simulate the wear under external force. The sample was moved at a constant speed of 20cm as a wear cycle. After 15 wear cycles, although some nanosheets on the surface were damaged, the overall hierarchical pit structure was not significantly damaged (see Figure 3 ). The cross-sectional height of the samples before and after wear was measured, and it was found that the height of the micro-nano hierarchical pit structure only decreased slightly (see Figure 4 ), but the overall structure remains basically intact.

[0063] Through the verification of the above-mentioned embodiments 1 to 3, embodiment 1 can achieve the best anti-icing effect, and the ice extension time can be close to 2 hours; embodiment 2 can achieve the best ice-repelling effect, and the minimum ice adhesion strength is 1.4kPa; embodiment 3 can achieve the best wear resistance effect, and after multiple wears, the overall layered pit structure has not been significantly damaged. Good anti-icing, ice-repelling and wear resistance have important application value in the field of anti-icing and de-icing.

[0064] In order to better illustrate the beneficial effects that can be achieved by the ice-phobic and wear-resistant micro-nano layered structure and the preparation method thereof of the present invention, the technical solution of the present invention is further analyzed with several comparative examples below.

[0065] Comparative Example 1:

[0066] Based on Example 3, the difference is that this comparative example does not use femtosecond laser to process the micro-cone structure, that is, this comparative example directly processes a single-layer pit structure on the surface of the aluminum alloy substrate, and at the same time, the surface of the aluminum alloy substrate is subjected to the same fluorination treatment as in Example 3. The obtained structure is shown in FIG. Figure 5 .

[0067] Comparative Example 2:

[0068] Based on Example 3, the difference is that in this comparative example, after the micro-cone structure is processed on the surface of the aluminum alloy substrate, the micro-pit structure is not processed by femtosecond laser, and the surface of the aluminum alloy substrate is subjected to the same fluorination treatment as in Example 3. The obtained structure is shown in FIG. Figure 6 .

[0069] See also Figure 7 In order to verify the ice-repellent performance of Comparative Examples 1 to 2, the samples were placed horizontally in a refrigerator at a temperature of -18°C and a relative humidity of 80%. A transparent uncovered square tube of 6mm×6mm×30mm was used as a mold and placed on the sample. Ultrapure water was added to the mold and frozen for 4 hours until it was completely frozen, and then the icicle was pushed at a constant speed with a thrust gauge. The peak force required to push down the icicle was recorded and its ice adhesion strength was calculated.

[0070] See also Figure 8 In order to verify the wear resistance of comparative examples 1 to 2, 1000-grit sandpaper was selected and placed under the sample, and the sample was pasted on the bottom of a 100g weight to simulate the wear under the external force. The sample was moved at a constant speed of 20cm as a wear cycle, and the ice adhesion strength after 15 wear cycles was recorded.

[0071] Through the verification of the above-mentioned comparative examples 1 to 2 and Example 3, the ice-phobic wear-resistant micro-nano hierarchical structure provided by the present invention can imitate the structure of lotus leaves and rose petals by femtosecond laser and boiling water treatment, and its ice adhesion strength is much lower than that of comparative examples 1 and 2, which is reduced by 77.4% compared with comparative example 1 and 36.4% compared with comparative example 2. After multiple wear, the ice adhesion strengths of comparative examples 1 and 2 are close to 20kPa and 40kPa respectively, while the ice adhesion strength of Example 3 is still lower than 10kPa. It shows that the present invention is not a simple superposition of the effect of the pit structure of comparative example 1 and the effect of the micro-cone structure of comparative example 2. The presence of the multi-level structure in the micro-nano hierarchical structure provided by the present invention enables the droplets to maintain a stable Cassie-Baxter state at low temperatures, reduces the ice adhesion strength, and achieves the ice-phobic effect; at the same time, the micron-level hierarchical structure provides a good mechanical support for the surface, which can resist the mechanical wear of the micron-level sheet structure inside the pit and achieve good wear resistance.

[0072] The number of devices and processing scales described here are used to simplify the description of the present invention. Applications, modifications and variations of the present invention will be obvious to those skilled in the art.

[0073] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes, and they can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the illustrations shown and described herein.

Claims

1. A method for preparing a laser-processed ice-phobic wear-resistant micro-nano hierarchical structure, characterized in that: Here are the steps: S1. Using a femtosecond laser to process a micro-cone array of the same size and spacing on the surface of a substrate, a surface with distributed micro-cones and smaller cluster structures is obtained; the laser beam of the femtosecond laser is perpendicular to the surface of the substrate, and the laser beam scans the surface line by line in a scanning path of perpendicular cross lines; S2. Using a femtosecond laser to process a micro-pit structure of uniform size on the top of the micro-cone to obtain a layered pit structure and a smaller cluster structure, wherein the laser beam of the femtosecond laser is perpendicular to the substrate surface, and the laser beam is scanned point by point on the surface in a parallel manner; S3, using a boiling water treatment method, immersing the substrate treated by S2 in boiling water for a certain period of time, and obtaining a densely distributed submicron-level flaky structure on the surface of the substrate; S4, performing fluorination treatment on the substrate treated in S3; In S4, the substrate surface is fluorinated using low surface energy 1H,1H,2H,2H-perfluorodecyltriethoxysilane for modification; The specific method for fluorination treatment of the substrate surface comprises: immersing the substrate in a mixture of 1H, 1H, 2H, 2H-perfluorodecyltriethoxysilane and anhydrous ethanol, wherein the volume ratio of 1H, 1H, 2H, 2H-perfluorodecyltriethoxysilane to anhydrous ethanol is 1:50, and the immersion time is 2 to 4 hours; The ice-repellent and wear-resistant micro-nano hierarchical structure includes: A substrate, the surface of which is processed with layered pits arranged in a periodic array, the surface and interior of the layered pits are randomly distributed with micron-scale clustered particle structures, and the surfaces of the layered pits and the micron-scale clustered particles are closely arranged with submicron-scale flaky structures; The surface of the substrate is modified by fluorination.

2. The method for preparing the laser processed ice-phobic wear-resistant micro-nano hierarchical structure according to claim 1, characterized in that: In S1, the spot diameter of the femtosecond laser is 10-20 μm, the pulse energy is 150-250 mW, the scanning speed is 0.001-0.004 m / s, and the scanning interval is 40-80 μm.

3. The method for preparing the laser processed ice-phobic wear-resistant micro-nano hierarchical structure according to claim 1, characterized in that: In S2, the spot diameter of the femtosecond laser is 10-20 μm, the pulse energy is 90-130 mW, the scanning time is 18000-32000 μs, and the scanning interval is 40-80 μm.

4. The method for preparing the laser processed ice-phobic wear-resistant micro-nano hierarchical structure according to claim 1, characterized in that: In S3, the boiling water treatment time is 60-180 min, and the boiling water temperature is 100-130°C.

5. The method for preparing the laser processed ice-phobic wear-resistant micro-nano hierarchical structure according to claim 1, characterized in that: The substrate is an aluminum sheet or an aluminum alloy sheet with a thickness greater than 120 μm.

6. The method for preparing the laser processed ice-phobic wear-resistant micro-nano hierarchical structure according to claim 1, characterized in that: The stratification pits have the same size, with a height of 20-90 μm, a bottom diameter of 20-60 μm, a center distance between adjacent stratification pits of 20-120 μm, a central pit depth of 10-60 μm at the top of the stratification pit, and a central pit diameter of 10-40 μm.

7. An application of an ice-phobic wear-resistant micro-nano hierarchical structure, wherein the ice-phobic wear-resistant micro-nano hierarchical structure is prepared by the preparation method of the laser-processed ice-phobic wear-resistant micro-nano hierarchical structure according to any one of claims 1 to 6, characterized in that: The ice-repellent and wear-resistant micro-nano layered structure is applied to aircraft aluminum skin or aluminum alloy skin to achieve ice protection and deicing on the aircraft surface.

Citation Information

Patent Citations

  • Super-hydrophobic anti-icing aviation aluminum alloy surface and production method

    CN111846193A

  • White clover imitated surface with ultralow ice adhesion strength and preparation method and application of white clover imitated surface

    CN116329735A